2023
DOI: 10.3389/fpls.2023.1226911
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated editing of PHYTOENE DESATURASE gene in onion (Allium cepa L.)

Pawan Mainkar,
Tushar Kashinath Manape,
Viswanathan Satheesh
et al.

Abstract: IntroductionClustered regularly interspaced short palindromic repeats (CRISPR)/ CRISPR-associated protein 9 (Cas9) is a precise genome editing tool used to introduce genetic modifications in a wide range of crop species. Thus far, there is no report of CRISPR/Cas9-mediated genome editing in onions (Allium cepa L.). MethodsIn the present study, we targeted two exons of the gene coding for Phytoene desaturase (AcPDS) in onion cv. Bhima Super. The sgRNA-carrying constructs were co-cultivated with 8-week-old embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The knockout of the PDS gene in many crop species resulted in a phenotype with pigmentation loss. Albino regenerants of cells with edited PDS gene have been obtained for Malus domestica plants, for diploid and octoploid strawberries, yams, and onion [50][51][52][53]. The regenerants of carrot cells with mutations in the region of the DcPDS and DcMYB113-like genes were depigmented [54].…”
Section: Carotenoid Synthesismentioning
confidence: 99%
“…The knockout of the PDS gene in many crop species resulted in a phenotype with pigmentation loss. Albino regenerants of cells with edited PDS gene have been obtained for Malus domestica plants, for diploid and octoploid strawberries, yams, and onion [50][51][52][53]. The regenerants of carrot cells with mutations in the region of the DcPDS and DcMYB113-like genes were depigmented [54].…”
Section: Carotenoid Synthesismentioning
confidence: 99%
“… 22 It has been targeted in many CRISPR/Cas mediated genome editing studies as a visible marker to standardize the delivery of CRISPR reagents into plant cells. 23 , 24 , 25 By inhibiting chlorophyll, carotenoid, and gibberellin production, the disruption of PDS results in photobleaching, albino phenotype, and dwarfism. 26 It also allows for simple screening of mutant lines.…”
Section: Introductionmentioning
confidence: 99%
“… 26 It also allows for simple screening of mutant lines. 27 , 28 Recent studies have shown the establishment of efficient genome editing using the PDS gene through the CRISPR/Cas9 system in several crops, including potato, 24 pea, 29 papaya, 30 coffee, 31 chickpea, 32 hop, 23 onion 25 and squash. 33 Nevertheless, the development of a biolistic-mediated CRISPR/Cas9-reagent delivery system using the PDS gene in chilli pepper has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%